Henry the 1/8 - Woods, Dave (London: Orchard, 2014)
Young Henry 1/8 is soccer-crazy. Henry 1/8 has a goal--to captain England in Ye First Worlde Cup! To win, his team of Young Lion Cubs must tackle the Potent Portuguese, the French Strikers, the Dutch Masters, and the Smashing Spaniards. Will the pint-sized prince bring soccer home?
Keywords: Adventure stories